Counseling Adlerian approach: a systematic literature review - Vonny Fatimah,; M. Ramli,; Fitri Wahyuni, (Technium Social Sciences Journal, 2024)
Individual psychology, which was pioneered by Alfred Adler, believes that humans have an innate drive to overcome their weaknesses so that they can develop their potential using self-actualization. This research aims to analyze research on the Adlerian counseling approach. The method used in this research is the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The data sources were obtained from Scopus and Crossref with a period of 2013 to 2023. The data sources obtained from Scopus were 59 articles and Crossref 145 articles, then the inclusion and exclusion data were reduced so that the data sources from Scopus were 3 articles and Crossref 11 articles. The results of this research indicate that Adlerian counseling has the same principles as a neuroscientific perspective. The implementation of Adlerian counseling cannot be separated from counseling techniques to help solve client or counselee problems. The discovery of a new counseling technique, namely Adventure Therapy, and supervision of the implementation of Adlerian counseling aims to develop counseling skills in counselors. The Adlerian counseling approach is effective in reducing levels of anxiety and hopelessness.